Prognostic value of the platelet-to-lymphocyte ratio for recurrent hemoptysis following bronchial artery embolization in patients with ronchiectasis - Yuxin Duan; Weifan Sui; Zefeng Cai; Yimao Xia; Jianyun Li; Jianhua Fu (Medicine, 2026)
Hemoptysis is a potentially life-threatening complication commonly observed in patients with bronchiectasis, often necessitating bronchial artery embolization (BAE). However, recurrence following BAE remains a significant clinical challenge. The platelet-to-lymphocyte ratio (PLR), a readily available inflammatory marker, has shown prognostic value in various pulmonary diseases. This study aimed to investigate the association between PLR and hemoptysis recurrence in patients with bronchiectasis who underwent BAE and to develop a prognostic model based on PLR. This retrospective study included 127 patients with bronchiectasis-related hemoptysis who underwent BAE between January 2018 and April 2022. Clinical, laboratory, and imaging data were collected. Restricted cubic spline analysis was used to evaluate the relationship between PLR and recurrence. Kaplan–Meier analysis assessed recurrence-free survival between high and low PLR groups, based on a cutoff determined by receiver operating characteristic analysis. Feature selection was performed using Boruta, LASSO regression, and random forest algorithms. A prediction model was constructed using intersecting variables and validated by time-dependent receiver operating characteristic, C-index, calibration, and decision curve analysis. PLR was significantly associated with hemoptysis recurrence, with a dynamic relationship observed over time: a linear association in the early follow-up period became nonlinear thereafter ( P for overall